2017
DOI: 10.31106/jema.v14i02.524
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Third-Party Funds, Car, NPF and FDR Towards the Return on Assets of Islamic Banks in Indonesia

Abstract: The purpose of this research is to analyze the influence of third party funds, capital adequacy ratio (CAR), non performing financing (NPF) ,financing to deposit ratio (FDR) Of return on assets (ROA) during period of 2008-2013 syariah banks in indonesia. About 3 syariah banks in indonesia was taken as sample for this research. The data used for this research were obtained from the data of Quarterly Published Financial Report Period 2008 up to 2013. The analysis technique used is Linear Regression that aims for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 0 publications
3
29
1
2
Order By: Relevance
“…The results also showed that the amount of financing has a negative effect on ROA due to the high bank NPF. According to Abusharbeh (2014) also Kinanti and Purwohandoko (2017), an increase in funding leads to a rise in NPF, which further reduces ROA (Kinanti & Purwohandoko, 2017;Yusuf, 2017). Financing is the main source of bank income, therefore, the absence of barriers leads to a rise in financial growth (Fowowe, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results also showed that the amount of financing has a negative effect on ROA due to the high bank NPF. According to Abusharbeh (2014) also Kinanti and Purwohandoko (2017), an increase in funding leads to a rise in NPF, which further reduces ROA (Kinanti & Purwohandoko, 2017;Yusuf, 2017). Financing is the main source of bank income, therefore, the absence of barriers leads to a rise in financial growth (Fowowe, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This means that caution is needed in channeling financing to prevent inconsistencies. However, Sari and Murni (2016); Kinanti and Purwohandoko (2017); and Kassem and Sakr (2018) stated that loan to the ratio of third party funds has a positive effect on ROA. More specifically, Dang (2019) reported that an increase in loans had a positive effect on profitability.…”
Section: H3mentioning
confidence: 98%
See 1 more Smart Citation
“…The level of capital availability as measured by the CAR ratio shows a bank's potential ability to generate profits as the results of the study; (Zahrah et al, 2019); (Anggreni, 2014); (Shamki et al, 2016); (Nahar & Prawoto, 2017); (Kinanti, 2017); (Amelia, 2015); (Hantono, 2017); (Sabir et al, 2012); (Chou & Buchdadi, 2016) and (Alshatti, 2016). Research with the opposite result was carried out by (Sudiyatno, 2013); (Wibowo, 2013), while research (A. Rifqah & Hassan, 2019) got significant adverse results.…”
Section: Literature Reviewmentioning
confidence: 52%
“…This can be caused by the interrupt variables that can change the interaction of loans distribute by bank against bank profitability. Non-performing loans (NPL), net interest margin (NIM) and operating expenses on operating income (OEOI) are variables that can influence bank's profitability (Puspitasari, Setiadi, and Rizkiyanti 2015), (Junaeni 2017), (Kinanti and Purwohandoko 2017). Therefore, NPL, NIM and OEOI can mediate the effect of LDR on ROA.…”
Section: Introductionmentioning
confidence: 99%